THE CONCEPT AND FEATURES OF CONTRACT OF PAID MEDICAL SERVICES - Irina Mikhaylovna Vilgonenko; Yulia Nikolaevna Slepenok; Lyudmila Petrovna Stepanova (Современная наука и инновации)
The article concerns the issues regarding the contractual regulation of relations on the provision of medical services and the distribution of rights and responsibilities of the executor of medical services and the customer.